Case report of a patient with suspected COVID-19 with depression and fever in an epidemic stress environment - Rui Fu; Yueqin Zhang (General Psychiatry)
During the COVID-19 pandemic, the number of suspected cases, confirmed cases and those who passed away from the virus has been reported in major media and the internet, and has caused a high degree of tension. In addition, people’s outdoor activities have been limited, making it more difficult to find outlets for releasing stress. Under this situation, some people began to experience emotions of anxiety and depression. This article reports a case of depression with fever caused by the stress tension of the pandemic. The patient was highly suspected to have contracted COVID-19. The reported patient, who had a history of depression and had been to Wuhan to attend an exam, showed obvious pre-exam anxiety under the epidemic situation, which gradually increased the patient's pressure and then caused some adverse symptoms, such as insomnia, anxiety, sweating and a reoccurrent fever. Local community authorities paid close attention to him and later sent him to a general hospital in Jingmen for quarantine and treatment, as he was suspected of having COVID-19. After being hospitalised for half a month, he was ruled out from having ‘COVID-19’ and was cured of depression and discharged from the hospital. From this case, we can realise that, under the situation of the epidemic, people are easily prone to insomnia, anxiety and even depression. As clinicians in general hospitals, especially when encountering large emergencies, we must carefully inquire about the patient’s medical history while strengthening our understanding of psychiatric knowledge to improve the recognition rate for depression.